The collective lie in ketamine therapy: a call to realign clinical practice with neurobiology - Miller, Charles; Lopes, Bryan; McCurdy, Anna (Frontiers in Psychiatry, 2025)
In recent years, ketamine therapy has become increasingly entangled with psychedelic culture, leading to widespread misinterpretation of its therapeutic mechanism. This manuscript challenges the prevailing narrative that positions ketamine as a consciousness-expanding agent or psychotherapy enhancer, highlighting the discord between this view and ketamine’s well-established neurobiological function as an N-methyl-D-aspartate (NMDA) receptor antagonist that promotes neuroplasticity. Drawing on recent research and clinical data, the article argues that the acute dissociative experience often emphasized in ketamine-assisted psychotherapy (KAP) is neither necessary nor sufficient for therapeutic success. Instead, it describes how meaningful, lasting improvement in mental health outcomes requires plasticity-driven reorganization in the days following ketamine administration, not from insights gleaned during dissociation. By prioritizing subjective experience over biological timing, current KAP practitioners risk distorting memory, reinforcing maladaptive narratives, and undermining the potential of psychoplastogenic treatments. This article calls for a shift toward evidence-based protocols that align clinical practice with neurophysiology, advocating for greater education, standardization, and scientific rigor in ketamine therapy.